ROFIL DAN PREFERENSI WISATAWAN DI DESTINASI WISATA DANAU KEMBAR KABUPATEN SOLOK SUMATERA BARAT - Febriani, Salma; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Tourism in Indonesia has extraordinary diversity and potential and is one of the main sources of economic development in various countries. One of the destination that has potential to be developed is the twin lakes tourist destination located in Alahan Panjang, Solok Regency, West Sumatera. The profile and Preferences of tourist at this destination will be the main focus of ths study. This study aims to find out about the profile and preferences of tourist visiting the Twin Lakes tourist Destination in Solok Regency. This study uses a quantitative method with a descriptive approach and data is obtained through a survey of guest visiting this tourist destination using a questionnaire based on several point related to the profile and preference such as age, occupation, area of origin education, anda reasons that make the Twin lake tourist destination a choice for the tourist to visit. The result of the study show that knowing the profile and preferences of tourist can be used as one way to help manager develop tourist destination so that they can be in accordance with that tourist expect in the future. Keywords: Tourism, Profile and Preferences, Tourist Destinations, Tourists.